Ms. Marvel. Beyond the limit - Ahmed, Samira (Fiction writer) (Marvel Worldwide, Inc., 2022)
"After an interdimensional explosion at her cousin's lab, Kamala Khan suddenly has a doppelganger to deal with! As Ms. Marvel, it's her duty to help out the newcomer -- but something doesn't feel quite right. Kamala's powers are on the fritz, and she suspects that this new hero-in-training isn't trustworthy. Can a misfiring Ms. Marvel protect her good name when the copycat goes wild? And why has everything around her ... turned into a Bollywood set?! Why is everyone singing -- and how can she make it stop?" -- Back cover.